A new species of Pabstiella (Pleurothallidinae, Orchidaceae) from Ecuador - Ponert, Jan; Andrade, Mario Portilla; Karremans, Adam P.; Chumová, Zuzana; Trávníček, Pavel (Phytotaxa, 2021)
Pabstiella elegans is newly described based on cultivated material originally collected near Chaucha in Ecuador. It belongs to the group of small, creeping species of Pabstiella section Mentosae and differs from its closest relatives by the two-times larger flower and unusual colour of its sepals, which are creamy white with red dots. It also differs in the genome size (1C-value = 0.537 pg), which is 10.5% higher than its sister species, P. aryter. Phylogenetic placement is supported by an analysis based on nuclear ribosomal ITS and plastid matK regions.